2017
DOI: 10.1007/s00213-017-4659-9
|View full text |Cite
|
Sign up to set email alerts
|

Choice between variable and fixed cocaine injections in male rhesus monkeys

Abstract: Rationale The schedule of drug availability may enhance choice of a drug. In nonhuman subjects, reinforcers are chosen more often when available under variable schedules of reinforcement relative to fixed schedules. Objective To determine whether variable-drug access is an important determinant of cocaine choice by manipulating the schedule, drug dose, and combination of schedule + dose. Method Four male rhesus monkeys chose between cocaine doses (0.025–0.4 mg/kg/injection). In control conditions, the sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…Thus, "indifference" represented here is the result of averaging from the extremes. We have found that a biased pattern of behavior is typical under identical FR schedules when choice is between identical reinforcers or between different reinforcers (e.g., food and drug) that are subjectively equivalent (Freeman et al, 2014;Huskinson et al, 2016Huskinson et al, , 2017Huskinson et al, , 2019Woolverton, 2003) and is consistent with predictions of the matching law (Baum, 1974;Herrnstein, 1961), because exclusive choice of one option maximizes reinforcement, as does allocating choice among both options. Importantly, the test lever was held constant between Fixed and Variable conditions so that a lever bias had an equal impact on choice across conditions.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…Thus, "indifference" represented here is the result of averaging from the extremes. We have found that a biased pattern of behavior is typical under identical FR schedules when choice is between identical reinforcers or between different reinforcers (e.g., food and drug) that are subjectively equivalent (Freeman et al, 2014;Huskinson et al, 2016Huskinson et al, , 2017Huskinson et al, , 2019Woolverton, 2003) and is consistent with predictions of the matching law (Baum, 1974;Herrnstein, 1961), because exclusive choice of one option maximizes reinforcement, as does allocating choice among both options. Importantly, the test lever was held constant between Fixed and Variable conditions so that a lever bias had an equal impact on choice across conditions.…”
Section: Resultssupporting
confidence: 65%
“…This was driven largely by conditions in which the Variable Cocaine or Variable Food option were chosen less frequently (i.e., low-and high-dose conditions) compared with conditions in which the variable option was chosen more frequently (i.e., middle-dose conditions). Fewer VR trials resulted in skewed means, and we have seen this before (Huskinson et al, 2017). However, these values are still close to the programmed VR values.…”
Section: Fixed and Variable Schedules Of Food And Cocainesupporting
confidence: 75%
See 3 more Smart Citations